Assessing the Compliance of Indonesian Marriage Laws with CEDAW Principles - Aditya Restu Hapriyanto; Desi Syamsiah (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to assess the extent to which marriage law in Indonesia accommodates the principles of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). CEDAW, which Indonesia ratified in 1984, sets out various principles to ensure gender equality in all aspects of life, including marriage and family. However, the implementation of these principles in Indonesian marriage law still faces various challenges. Using a normative legal analysis approach, this study evaluates existing marriage regulations in Indonesia, including Law Number 1 of 1974 concerning Marriage. It examines whether these regulations comply with the provisions of CEDAW. This study also analyzes the gap between the principles of CEDAW and legal practices applied in Indonesia, taking into account cultural, social, and political factors that influence the implementation of these principles. The results of the study indicate that although there has been some progress in the equality of marriage rights, there are still inconsistencies in several aspects, such as restrictions on the age of marriage and women's rights in family decisions. Therefore, this study recommends a revision of several legal provisions in Indonesia to be more in line with the principles of CEDAW, to improve the protection of women's rights in the context of marriage.